Fast software encryption : 14th International Workshop, FSE 2007, Luxembourg, Luxembourg, March 26-28, 2007 : revised selected papers - FSE; International Association for Cryptologic Research; Biryukov, Alex (Lecture Notes in Computer Science, 2007)
This book contains the thoroughly refereed post-proceedings of the 14th International Workshop on Fast Software Encryption, FSE 2007, held in Luxembourg, Luxembourg, March 2007. It addresses all current aspects of fast and secure primitives for symmetric cryptology, covering hash function cryptanalysis and design, stream ciphers cryptanalysis, theory, block cipher cryptanalysis, block cipher design, theory of stream ciphers, side channel attacks, and macs and small block ciphers.